Dad-aismo. La scuola e la didattica a distanza - Bruno Moroncini (Laboratoire Italien)
The thesis developed in this article is that distance learning represents an important stage in the process of uprooting the human race, restoring its primitive nomadism, which has now been transformed by information highways and digital networks. This latest form of freedom from the tyranny of place follows the end of serfdom and of the hic et nunc in the enjoyment of works of art. It also changes the power relations that have been reinforced in modern schools and frees learning from the confines of the classroom. The author reiterates the criticism of modern schools shared by different figures such as Pasolini and Ivan Illich, for whom the objective of education was not the acquisition of knowledge that would set the lower social classes free, but the creation of mass conformity which was not free from criminal temptations.